Navigating the Merdeka Curriculum in EFL Class at Islamic Junior High School: Teachers’ Perception and Challenges - Abas Rosadi; Condro Nur Alim (Journal of English Language Teaching and Linguistics, 2025)
This research investigates EFL teachers' perceptions of the Merdeka Curriculum (MC) in State Islamic Junior High Schools (SIJHS) in Purbalingga regency, focusing on implementation challenges and solutions. Using a qualitative design, data were collected from six EFL teachers through interviews, classroom observations, field notes, and document analysis. Findings indicate that (1) teachers held positive perceptions of the MC, but (2) faced challenges due to limited understanding of the curriculum, delayed implementation, and difficulties navigating the Platform Merdeka Mengajar (PMM), exacerbated by insufficient motivation and lack of mandatory regulations for its use. To address these issues, the study recommends teacher training on effective MC implementation, collaboration through district teacher study groups (MGMP), meaningful teaching processes, regular evaluations, and intensive guidance to engage with PMM. These measures can enhance self-directed learning, teacher professionalism, independent learning, webinar participation, and overall professional development, facilitating successful MC implementation.